Factors Influencing Consumer Loyalty: A Study in the Tech Industry - Gan Kia Hui; Haslindar Ibrahim; Lee Sze Jie; Lee Xin Wen; Li Guowei; Li Baochen; Firanda Leiliya Putri; Fito Firman Syah; Somya Gupta (Asia Pacific Journal of Management and Education (APJME), 2024)
Since Apple’s 2010 release of the revolutionary iPhone 4, the brand has become a dominant force in the tech industry, fostering high customer loyalty through its integrated, secure ecosystem. This study aims to explore the factors driving Apple’s consumer loyalty in Malaysia, focusing on brand experience, brand innovativeness, social influence, perceived value, and brand trust. Primary and secondary data were collected, and a digital survey of 150 Malaysian Apple users provided insights into their loyalty determinants. Using regression analysis, the findings reveal that perceived value and brand trust significantly and positively impact consumer loyalty, while brand experience, brand innovativeness, and social influence show minimal influence. With an R-squared value of 0.596, the model suggests that nearly 60% of loyalty variance is explained by these factors, highlighting perceived value and trust as critical components. These results imply that Apple should prioritize enhancing perceived value and maintaining brand trust to strengthen consumer loyalty in competitive markets. Future research could explore additional factors like sustainability and community engagement to provide a fuller understanding of loyalty drivers in the tech industry.